The use of morphometric characters to discriminate populations of Heterorhabditis bacteriophora (Nematoda: Heterorhabditidae) - Soleimani, Ahmad; Kary, Naser Eivazian; Moslehi, Shalaleh (Zootaxa, 2023)
In a survey of entomopathogenic nematodes (EPNs) in the northwest of Iran, eleven isolates of Heterorhabditis bacteriophora were recovered mainly from the soil samples of apple orchards. The isolates were identified morphologically and molecularly. To unravel intraspecific variation, morphometric characters of different life stages, including hermaphrodite, female, male and infective juvenile (IJ), were evaluated to see efficiencies in discrimination of H. bacteriophora populations isolated from relatively limited geographical regions. Morphometric data were subjected to principal component analysis (PCA), canonical analysis (CAN), and also cluster analysis. Significant differences in morphometrics were recorded between the studied populations. The results of the PCA on IJ variables showed that the first two PC account for more than 99% of the total variance. Variables including distance from anterior end to the base of the pharynx (Es) and distance from anterior end to nerve ring (Nr) showed the highest factor loading. Cluster analysis put the studied populations in five well-defined groups. Resulted PC1 and PC2 for females account 63% of the total variance. Females variables include body length (L), distance from anterior end to excretory pore (EP), length divided by width (A), length divided by Es (B), length divided by tail length (C), and anal body width (Abw), tail length (TL), EP divided by TL ×100 (E) were effective in discrimination of the populations into three distinct groups. The first two PC from hermaphrodite variables accounted for 66% of the total variance. Variables include L, A, B, and C had efficient factor loading on PC1, and PC2. Cluster analysis of hermaphrodite morphometrics yielded five distinct groups among populations. For male variables PC1, and PC2 accounted 60.04% of the total variance, and body width, Abw, TL and, E were the most efficient in PC1 and PC2 was affected efficiently by Es and EP. The results of PCA showed that the highest discrimination among the studied H. bacteriophora population occurred with female variables.